The Role of Human Resource Management in Organizational Performance - Susanti, Andini; Bahiroh, Eloh (Indonesian Journal of Applied and Industrial Sciences (ESA), 2024)
In education, human resource management (HRM) is a strategic approach to managing the workforce involved in the learning process and student development. In the context of education, HR management includes a series of actions that include planning, organizing, directing, coordinating, and supervising educators, education personnel, and all components involved in managing the establishment organization. The main focus is to ensure the success and progress of education by maximizing the human potential involved. In the Indonesian language, “performance” comes from the word “basic work”, which means “the result of work”. Basically, performance is the quality and quantity of work achieved in carrying out their duties in accordance with the responsibilities given.